Clinical applications of AI-prediction tools in spine surgery: a narrative review - Mohammad Hamza Bajwa; Areeba Ahmed Samejo; Akbar Jaleel Zubairi (Journal of the Pakistan Medical Association, 2024)
Spine surgery has grown into a wide, complex field encompassing trauma surgery to deformity to tumours. Artificial intelligence (AI) based technology has been particularly useful in improving imaging-reporting and detection of predictive patterns. The purpose of this narrative review is to present practical approaches towards implementing upcoming AI spine research for clinicians to help improve practices, clinical throughput, and surgical decision-making. Keywords: Artificial Intelligence, Acute Care Surgery, Neoplasms, spine deformity, scoliosis, prediction